Return On Assets, Leverage, Company Size dan Tax Avoidance - Dharmayatri, Ni Wayan Shintya; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p12, 2021)
The purpose of this study was to determine the effect of return on assessment, leverage and company size on tax avoidance. This research was conducted on mining sector companies listed on the IDX in 2017-2019. The sampling method used was purposive sampling. The number of companies that met the criteria was 11 companies with 33 observations. Data collection was carried out by non-participant observation method. The data analysis technique used is multiple linear regression analysis. Based on the research results, it was found that return on assets and company size have a negative effect on tax avoidance, while leverage has a positive effect on tax avoidance. Keywords: Tax Avoidance ; Return On Assets; Leverage; Company Size.